GAMBARAN PENERAPAN INISIASI MENYUSUI DINI PADA IBU BERSALIN - Ambarwati Ambarwati; antin yohana (Jurnal Profesi Keperawatan, 2018)
Abstract Early breastfeeding initiation is a skin to skin action between infants and mothers by way of directly placing newborn infants in their mother's breasts and letting the baby crawl to find mothers breast feeding (approximately 60 minutes) to improve maternal and infant closeness. Early breastfeeding initiation is performed immediately at birth, without delaying the activity of weighing or measuring the baby. Babies also should not be cleaned, just dried. A description of knowledge about early breastfeeding initiation in well matched maternal women, focusing on its purpose for maternal and infant closeness. The description of attitude about the implementation of early breastfeeding initiation strongly support the initiation of early breast feeding. The description of the practice of early breastfeeding initiation in maternal mothers is good and appropriate standard operating procedures in the delivery room. Appropriate and support government regulation to succeed exclusive breastfeeding and in order to reduce maternal and infant mortality. The benefits of Early breastfeeding initiation management include lowering infant mortality, preventing infant hypothermia, early immunization, strengthening the mother's and children's inner bonds, preventing allergic diseases, stimulating the release of the hormone oxytocin, reducing postpartum maternal bleeding, stimulating the psychomotor development of infants, reducing the risk of developing breast and ovarian cancers in the mother. Key notes : breast feeding , early breastfeeding initiation, maternal women,   Intisari Inisiasi menyusui dini adalah suatu tindakan kulit ke kulit antara bayi dan ibu yang dilakukan dengan cara langsung meletakkan bayi baru lahir didada ibunya dan membiarkan bayi merayap untuk menemukan putting susu ibu menyusu (lebih kurang 60 menit) untuk meningkatkan kedekatan ibu dan bayi. Inisiasi menyusui dini dilakukan langsung saat lahir, tanpa boleh ditunda dengan kegiatan menimbang atau mengukur bayi. Bayi juga tidak boleh dibersihkan, hanya dikeringkan. Gambaran pengetahuan tentang inisiasi menyusui dini pada ibu bersalin kategori baik, berfokus pada tujuannya untuk kedekatan ibu dan bayi. Gambaran sikap tentang penerapan inisiasi menyusui dini sangat mendukung dilaksanakan inisiasi menyusui dini pada ibu bersalin. Gambaran praktik penerapan inisiasi menyusui dini pada ibu bersalin sudah baik dan sesuai standar operasional prosedur di ruang bersalin. Sesuai dan mendukung peraturan pemerintah untuk mensukseskan ASI Eksklusif serta dalam rangka menurunkan angka kematian ibu dan bayi. Manfaat dari penatalaksanaan Inisiasi menyusui dini yaitu menurunkan angka kematian bayi, mencegah hipotermia bayi, imunisasi dini, mempererat ikatan batin ibu dan anak, mencegah penyakit alergi, merangsang pengeluaran hormon oksitosin sehingga mengurangi perdarahan ibu postpartum, merangsang perkembangan psikomotorik bayi, mengurangi risiko terkena kanker payudara dan ovarium pada ibu. Kata kunci: Ibu Bersalin, Inisiasi Menyusui Dini, Kedekatan ibu dan bayi